Hydrogen peroxide masks the bitterness of chlorhexidine mouthwash without affecting its antibacterial activity - Widhunya Mathurasai; Panida Thanyasrisung; Sireerat Sooampon; Benjar Issaranggun Na Ayuthaya (Wolters Kluwer Medknow Publications, 2019)
Background: Chlorhexidine (CHX) is an antiseptic mouthwash widely used as the gold standard for inhibiting plaque formation. However, the bitter taste of CHX limits patient compliance. We developed a 0.12% CHX and 1.5% hydrogen peroxide (H2O2) mouthwash that masked the bitter taste of CHX. This study evaluated the antibacterial activity and subject satisfaction of the developed mouthwash. Materials and Methods: Three mouthwashes were used as follows: (1) a commercial 0.12% CHX mouthwash, (2) a prepared 0.12% CHX mouthwash containing 1.5% H2O2, and (3) a prepared 0.12% CHX mouthwash. A disc diffusion assay was performed to determine the antibacterial activity of each mouthwash against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans. To assess subject satisfaction with each mouthwash, a satisfaction questionnaire was completed immediately after rinsing with each mouthwash. Results: The antibacterial activities of the three mouthwashes were similar. Moreover, the questionnaire results revealed that the level of satisfaction was significantly higher for the 0.12% CHX/1.5% H2O2 mouthwash compared with the other mouthwashes. Conclusion: The 0.12% CHX/1.5% H2O2 mouthwash revealed a similar antibacterial activity as the CHX standard against periodontal disease pathogens. In addition, the subjects were more satisfied with the new formula compared with 0.12% CHX alone. These data suggest that the 0.12% CHX/1.5% H2O2 formulation is an alternative antibacterial mouthwash to avoid the unpleasant CHX side effects.